Narrative Review of the Effect of Endorphin Massage and Oxytocin Massage on Pain Intensity in Maternity Women - Selian, Rada Almina; Hardisman, Hardisman; Yulizawati, Yulizawati; Firdawati, Firdawati; Iffah, Uliy (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Childbirth is the effort or process of expelling a full-term baby which is often accompanied by pain caused by contractions in the uterus. From the research results, it was found that 32% of 300 women who gave birth during the active phase experienced severe pain, 57% moderate pain, and 11% mild pain. Evidence shows that fear of vaginal childbirth and anxiety experienced by many women during their pregnancy. Therefore, it then led to their decision to choose other methods of birth such as Section Caesarea (SC). The effects of anxiety during labor could potentially result in excessive levels of catecholamines causing decreased blood flow to the uterus, decreased uterine contractions, decreased blood flow to the placenta, decreased oxygen available to the fetus, and can increase the length of labor. One of alternative methods of dealing with pain during the labor process is using non-pharmacological such as endorphin massage and oxytocin massage. Purpose: The aim of this literature study was to present information about the effect of endorphin massage and oxytocin massage on the intensity of pain among mothers giving birth. Methods: This research method was a literature review study. Journal searches were carried out by applying online database such as ScienceDirect, Google scholar, Pubmed, Scopus, Portal Garuda. Articles were selected based on inclusion and exclusion criteria. Result: The study investigated the influence of endorphin and oxytocin massages on pain intensity in maternity mothers during childbirth, revealing a significant reduction in pain levels following the administration of these massages. Both endorphin and oxytocin massages were found to alleviate pain, induce relaxation, and promote feelings of comfort and calmness, thereby facilitating a smoother birth process. Conclusion: The influence of endorphin massage and oxytocin massage is useful in reducing pain in maternity mothers